Chemical looping with air separation (CLAS) in a moving bed reactor with CuO/ZrO2 oxygen carriers. (March 2018) - Ku, Young; Wu, Hsuan-Chih; Chang, Chia-Wei; Shiu, Shr-Han
Highlights: A moving bed reactor was employed as fuel reactor using Cu-based oxygen carriers. Zirconia is employed as support to improve the properties of oxygen carrier. Graphite used as solid fuel for CLOU with CuO/ZrO2 oxygen carriers was explored. High oxygen carrier conversion was reached by moving bed operation. Roughly 6.5 vol.% of oxygen concentration was released for CuO/ZrO2 reduction. Abstract: Zirconia supported CuO oxygen carriers were prepared for carrying out chemical looping with oxygen uncoupling (CLOU) and chemical looping with air separation (CLAS) operation in a thermogravimetric analyzer (TGA), a fixed bed reactor and a moving bed reactor (MBR). In this study, graphite used as solid fuel for CLOU with CuO/ZrO2 oxygen carriers was also explored in a fixed bed reactor. 40 wt.% CuO/ZrO2 particles sintered at 1000 °C revealed reasonable reactivity without noticeable agglomeration as observed. For fixed bed operation, time required for graphite combustion with CuO/ZrO2 was decreased for experiments conducted at higher reaction temperatures. For experiments carried out in the moving bed reactor, the oxygen concentration and oxygen molar flow rate in the outlet stream can be adjusted by varying operating temperatures, CuO/ZrO2 flow rate, and carrier gas (N2 ) flow rate. Therefore, moving bed reactors are technically feasible to serve as fuel reactor for chemical looping with air separation.